Knowledges on Thyroid Cancer - Engin, Omer (IntechOpen, 2019)
Thyroid cancer is being increasingly diagnosed nowadays. This situation has attracted the attention of scientists and physicians alike and new applications in diagnosis and treatment are being developed and used. There are many cases associated with thyroid cancer and in this book, thyroid cancer is examined in various aspects.